Membumikan Maqasid Al-Shar’iah Sebagai Basis Ijtihad Kontemporer - Wahid Ahtar Baihaqi (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
According to Jaser Audah, the maqasid methodology is a moderate understanding among literalism of zahiriyyah and deconstruction of historians. Maqasid approach seeks to bring Islamic law that not only oriented to the side of humanity with divinity but also makes maslahat as the last consideration. In operation, the maqasid shariah maqasid positioned higher level of textual implications (dilalah al-nash), the means that when a law of textual implication not affect real maslahat, it must be done in order to realize the maslahat of reinterpretation. In addition, in the process also should pay attention to the rules of thinking maqasid grouped into four; 1) all the provisions of the shariah has an illah, purpose, and maslahat. 2) determination of maqasid shariah has to use theorem (dalil). 3) hierarchy of maslahat and mafsadah. 4) separation between Maqasid with wasilah to maqasid.